2010
DOI: 10.1111/j.1365-2753.2009.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of therapeutic control in a Pakistani population with hypertension

Abstract: Patients being treated at primary health care centres in Pakistan have inadequate control of high blood pressure. Evidence-based continuous education of primary health care physicians is a necessary intervention for optimizing treatment strategies and achieving better therapeutic control of hypertension in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…One paper 24 had a larger sample size compared to the other five selected studies, however, this was still restricted to one city in Pakistan. Out of the six papers 14,[23][24][25][26]27 only one study recommended the need for a 'smoking cessation programme in order to prevent high rates of non-communicable diseases in the country'. With the exception of two papers 24,27 four others addressed sufficient details on ethical issues.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…One paper 24 had a larger sample size compared to the other five selected studies, however, this was still restricted to one city in Pakistan. Out of the six papers 14,[23][24][25][26]27 only one study recommended the need for a 'smoking cessation programme in order to prevent high rates of non-communicable diseases in the country'. With the exception of two papers 24,27 four others addressed sufficient details on ethical issues.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…Saleheen et al 25 Good knowledge identified as a risk factor is associated with better improvement in health outcomes Individual habits are influenced by their knowledge and attitude towards these behaviours Lack of appropriate health education has been linked with lack of therapeutic control in hypertensive patients People with hypertension necessitate the development of national education campaigns to increase the awareness on healthy lifestyle Improved knowledge and change in health attitude will bring significant decline in rates of hypertension and smoking Tassaduqe et al 27 Despite less knowledge on lifestyle modification, the Pakistani population has improved their knowledge level with health education Mahesar et al 24 Education and counselling by physicians has helped in developing effective strategies to deal against cardiovascular burden Socio economic status (n=3) Khan & Thaver 23 Socio economic disadvantage has a relationship with poor health and chronic illness Education and social status captured as an important dimension to make healthy choices Socio economic position and positive family history of smoking reported to increase in risk of cardiovascular burden Individual behaviour correlates with socio economic status (e.g. cigarette smoking) Smoking and hypertension are related to poor-low socio economic groups or having an adverse lifestyle Qamar et al 14 People among poor and middle socio economic groups smoke all types of tobacco products frequently due to lack of knowledge on smoking hazards Positive family history of smoking has associations with enhanced addiction of tobacco and more risk of cardiovascular damage Social group hypertension rate has appeared as common due to the usage of tobacco products Tassaduqe et al 27 Relationship between smoking, hypertension and social status are linked More research is needed to explore these parameters Individual behaviour is linked with control and prevention of hypertension Types of tobacco products (n=1) Shafique et al 26 Regardless of socio economic status, people are more prone towards alternative forms of tobacco products such as water pipe tobacco Flavouring of tobacco and charcoal has not appeared as alternatives to reduce harmful effects of smoking All tobacco products are related to high blood pressure in all age groups Lack of awareness Lack of awareness was one of the core themes that emerged from this review.…”
Section: Study Findings Lack Of Awareness (N= 3)mentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 In these countries, the smoking prevalence in males is approximately 48%; among women this is significantly lower (20%). 13 Similar to Western countries, in SEA, the incidence and prevalence of obesity (12e18%) 14e16 and of diabetes (10e15%) are also increasing.…”
mentioning
confidence: 99%